IMPLEMENTATION OF POLICE DISCRETION IN CRIMINAL LAW ENFORCEMENT IN ANARCHIC DEMONSTRATIONS - Siregar, Salwa Ramadhani; mahanani, Anajeng Esri Edhi (JARES (Journal of Academic Research and Sciences), 2024)
Police discretion is the authority of members of the police to take a policy in certain situations that require their own judgment as long as it does not violate statutory provisions. It aims to guard, maintain order and ensure public security. However, policies issued often raise pros and cons, especially when enforcing criminal law in securing demonstrations. The community considers that the actions taken are a form of hindering the achievement of their aspirations. This condition eventually led to riots during demonstrations which could threaten the safety of the demonstrators, police officers, as well as those at the location of the action. So that in this situation police discretion can be issued to prevent and deal with various threats that occur. This study uses an empirical juridical method, namely direct research conducted by studying the applicable legal rules with real events that occur in society. The results of this study explain related considerations, procedures, to obstacles and efforts made in the application of discretion by members of the police in overcoming anarchic demonstrations